Site-specific nutrient management is a key for enhancing productivity of rapeseed-mustard in India - Mahesh C Meena,; BS Dwivedi,; SP Datta, (Journal of Oilseed Brassica, 2026)
In India, rapeseed-mustard alone contributes in total oil production to the extent of about 24% with its averageproductivity of about 1.00 t ha-1. Analysis of 1601 soil samples from major mustard growing areas representing14 agro-ecological sub-regions (AESRs) indicated widespread multi-nutrient deficiency involving 2 to 6 nutrientsincluding NK, NKS, NKB, NPKS, NKSZn and NPKSZnB. Incidence and expansion of such multi-nutrientdeficiencies in Indian soils owing to inadequate and unbalanced nutrient input through fertilizers is consideredone of the major constraints in enhancing productivity of oilseed crops. In this context, different nutrientsupply options namely T1: SSNM; T2: State ad-hoc recommendation plus potassium (SR) + K; T3: SR; T4:Farmer’s fertilizer practice (FFP) + K; and T5: FFP were evaluated in Lohtaki village district Gurgaonrepresenting AESR 4.1 with pearlmilet-mustard cropping system. On an average, mustard grain yield responsesover FFP across the experiments were the highest in SSNM (85%), followed by SR+K (40%) and SR(24%). Average net return over FFP in pearlmillet-mustard cropping system was higher(Rs. 43963 ha-1) under SSNM, followed by SR+K (Rs. 26092 ha-1) and SR (Rs. 15693 ha-1). In all theseexperiments, SSNM proved superior to state recommendation and farmers’ fertilizer practice in terms ofannual crop yields, nutrient recovery, soil fertility restoration and net economic returns. Site-specific nutrientmanagement (SSNM) seems to be one of effective ways to improve nutrient supplying capacity of soil andenhance the productivity of mustard, which in turn will help in achieving much needed self sufficiency inoilseeds production in India.